Chromatoid body mediated RNA regulation in mouse male germline - Meikar, Oliver (Annales Universitatis Turkuensis D 1099, 2013)
Male germ cell differentiation, spermatogenesis is an exceptional developmental process that produces a massive amount of genetically unique spermatozoa. The complexity of this process along with the technical limitations in the germline research has left many aspects of spermatogenesis poorly understood. Post-meiotic haploid round spermatids possess the most complex transcriptomes of the whole body. Correspondingly, efficient and accurate control mechanisms are necessary to deal with the huge diversity of transcribed RNAs in these cells. The high transcriptional activity in round spermatids is accompanied by the presence of an uncommonly large cytoplasmic ribonucleoprotein granule, called the chromatoid body (CB) that is conjectured to participate in the RNA post-transcriptional regulation. However, very little is known about the possible mechanisms of the CB function. The development of a procedure to isolate CBs from mouse testes was this study’s objective. Anti-MVH immunoprecipitation of cross-linked CBs from a fractionated testicular cell lysate was optimized to yield considerable quantities of pure and intact CBs from mice testes. This protocol produced reliable and reproducible data from the subsequent analysis of CB’s protein and RNA components. We found that the majority of the CB’s proteome consists of RNA-binding proteins that associate functionally with different pathways. We also demonstrated notable localization patterns of one of the CB transient components, SAM68 and showed that its ablation does not change the general composition or structure of the CB. CB-associated RNA analysis revealed a strong accumulation of PIWI-interacting RNAs (piRNAs), mRNAs and long non-coding RNAs (lncRNAs) in the CB. When the CB transcriptome and proteome analysis results were combined, the most pronounced molecular functions in the CB were related to piRNA pathway, RNA post-transcriptional processing and CB structural scaffolding. In addition, we demonstrated that the CB is a target for the main RNA flux from the nucleus throughout all steps of round spermatid development. Moreover, we provided preliminary evidence that those isolated CBs slice target RNAs in vitro in an ATPdependent manner. Altogether, these results make a strong suggestion that the CB functions involve RNA-related and RNA-mediated mechanisms. All the existing data supports the hypothesis that the CB coordinates the highly complex haploid transcriptome during the preparation of the male gametes for fertilization. Thereby, this study provides a fundamental basis for the future functional analyses of ribonucleoprotein granules and offers also important insights into the mechanisms governing male fertility.

Miesten sukusolujen kehittyminen, spermatogeneesi, on tärkeä ja monella tavoin poikkeuksellinen kehitysprosessi, joka tuottaa suunnattomia määriä geneettisesti yksilöllisiä siittiöitä. Spermatogeneesi on monimutkainen, tarkasti säädelty tapahtumasarja, mikä myös aiheuttaa teknisiä haasteita spermatogeneesin molekyylimekanismien tutkimisessa. Näin ollen prosessin yksityiskohdat ovat vielä pitkälti tuntemattomia. Eräs siittiön haploidien esiasteiden (pyöreät spermatidit) erityisominaisuus on niiden ainutlaatuisen runsas transkriptionaalinen aktiivisuus. Genomin aktiivinen ilmentyminen puolestaan edellyttää tehokkaita ja täsmällisiä RNA:n säätelymekanismeja. Pyöreiden spermatidien solulimassa sijaitsee epätavallisen suuri RNA:ta ja proteiineja sisältävä rakenne, kromatoidikappale (chromatoid body, CB), joka ilmaantuu juuri voimakkaimman transkriptioaallon aikana ja osallistuu RNA-säätelyyn. Tutkimuksen tavoitteena oli selvittää CB:n toimintaa siittiönkehityksen aikana. Tärkeänä osana tutkimusta kehitimme menetelmän, jonka avulla CB:t voidaan eristää hiiren kiveksestä. Menetelmä on yksinkertainen, nopea ja tehokas, ja sen avulla saadaan eristettyä toistettavasti rakenteeltaan ehjiä CB:ta, joiden puhtaus on hyvä ja määrä riittävä molekyylitason analyysiin. Jatkotutkimukset paljastivat, että suurin osa CB:n sisältämistä proteiineista on erilaisilla RNA-säätelyreiteillä toimivia RNA:ta sitovia proteiineja. Useat CB:n proteiineista pysyvät rakenteessa stabiilisti, mutta näytimme myös, että RNA:ta sitova proteiini SAM68 vierailee CB:ssa vain hyvin hetkellisesti tarkasti määritellyssä kehitysvaiheessa. Poistogeenisen hiirimallin avulla saimme selville, ettei SAM68 proteiinia kuitenkaan tarvita CB:n muodostumiseen. Tulostemme mukaan CB:een kulkeutuu suuri määrä RNA:ta kaikissa pyöreiden spermatidien kehitysvaiheissa. RNA-sekvenointi osoitti, että pienet piRNA (PIWI-interacting RNA) molekyylit ovat rikastuneet CB:ssa. Lisäksi CB sisältää suuren joukon erilaisia lähetti-RNA:ita ja aivan tuntemattomia intergeenisiä eikoodaavia RNA:ita. Analyysimme mukaan hallitsevin CB:n molekyylireiteistä on piRNAvälitteinen RNA-säätelyreitti, mutta myös lähetti-RNA:n prosessointiin liittyvät tekijät ovat vahvasti edustettuina. CB ei selvästikään ole vain passiivinen RNA:n varastointipaikka, vaan näytimme sen kykenevän ATP:stä riippuvaiseen RNA prosessointiin in vitro Kaikki tutkimuksen tulokset osoittavat, että CB on keskeinen RNA:n säätelykeskus, joka koordinoi sukusolujen erittäin monimuotoista transkriptomia. Tällä toiminnallaan CB osallistuu tärkeänä tekijänä miesten hedelmällisyyden ja sukusolujen geneettisen ja epigeneettisen informaation säätelyyn.